Juvenile Delinquents and the Juvenile Justice System in India: A Perception after the Fact - Nanjunda, Devajana Chinnappa (Humanities, Arts and Social Sciences Studies, 2019)
Experts felt Juvenile delinquents are basically resulting of societal malfunctions; all of them need particular care and close attention at their age. Since the last 50 years various studies have been done on the various aspects which help in understanding juvenile issues in different culture and society. The appearance of ‘culture of indifference’, aggression, violence, haughtiness, arrogance, depression, and irresponsibility among modern youth are leading to the depth of deviation among juveniles. Experts have provided a levelheaded picture of the very significant feature of contemporary society that ‘provokes youth towards crime’. In a nutshell; it can be said that juvenile delinquency is a consequence of the result of social changes and maladjustments with age as an an independent factor. Development experts felt latest developmental aspects including changing and new social, economic, political and cultural arrangements in the modern society owing to fast industrialization and urbanization are acting as causing factors for the speedy increase of delinquency. This paper is based on the review of the various literature and concludes that s. Juvenile Delinquents problems need to be handled with the new normative approaches.